2015
DOI: 10.1093/icvts/ivv312
|View full text |Cite
|
Sign up to set email alerts
|

The Warden procedure can be successfully performed using minimally invasive cardiac surgery without aortic clamping

Abstract: Currently, minimally invasive cardiac surgery has found widespread use even in congenital heart surgery. The number of defects, which can be corrected through a small incision or totally endoscopic, is on the rise. Nowadays, surgeons can repair atrial septal defect, ventricular septal defect, patent ductus arteriosus and other congenital heart defects using minimally invasive techniques. In this paper, we report 21 cases of successful repair of supracardiac partial anomalous right upper and middle pulmonary ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Iyer et al [5] compared single-patch and double-patch methods and revealed that the single-patch technique carried a higher risk of SVC stenosis. The results for the Warden procedure and its modifications have demonstrated a low rate of SVC obstruction, despite being a more complicated technique, which, in some cases, has necessitated enlargement of the anastomosis with a patch [2,3,8,10]. All authors emphasise the importance of wide cavoatrial anastomosis and careful resection of all intra-atrial trabeculations, which can cause future stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iyer et al [5] compared single-patch and double-patch methods and revealed that the single-patch technique carried a higher risk of SVC stenosis. The results for the Warden procedure and its modifications have demonstrated a low rate of SVC obstruction, despite being a more complicated technique, which, in some cases, has necessitated enlargement of the anastomosis with a patch [2,3,8,10]. All authors emphasise the importance of wide cavoatrial anastomosis and careful resection of all intra-atrial trabeculations, which can cause future stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…For the surgical approach, besides median sternotomy (23 patients in the DP and 21 in the WP group), right mid-axillary thoracotomy was also used in some patients from both groups (17 in the DP and 19 in the WP group) [10][11][12]. The choice of approach was based on the surgeon's preference.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, thoracoscopic cardiac surgery has been performed safely as a minimally invasive approach in larger children (15)(16)(17). The feasibility and safety of robotic cardiac surgery under cardiopulmonary bypass has remained limited in children due to technical limitations (7)(8)(9)(10)(18)(19)(20)(21)(22)(23). With the use of new generation systems, totally endoscopic robotic surgery can be a less invasive alternative to the other approaches in selected children with a suitable anatomy and cardiac pathology.…”
mentioning
confidence: 99%
“…Так, по результатам различ-ных исследований, частота ДСУ после процеду-ры Вардена составляет от 0 до 6,2% [7][8][9][10][11].…”
Section: Introductionunclassified